2001
DOI: 10.2527/2001.7992449x
|View full text |Cite
|
Sign up to set email alerts
|

Crude protein fractions in common vetch (Vicia sativa L.) fresh forage during pod filling.

Abstract: Crude protein (CP) of forages can be separated into fractions of differentiated abilities to provide available amino acids in the lower gut of ruminants. This knowledge is critical to develop feeding systems and to predict animal responses. We have measured during two growing seasons (1996 to 1997 and 1997 to 1998) the CP fractions of common vetch fresh forage with the objective being to assess the influence of maturity on concentration of CP fractions (as a percentage of total CP) and fraction yields. Fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
16
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 0 publications
9
16
0
2
Order By: Relevance
“…In the present study, this fraction ranged from 1.5 to 7.3 g kg −1 DM, averaging 4.6 g N kg −1 DM (Table 1). When expressed as a proportion of total N, fraction A varied between 80 and 390 g kg −1 , with a mean value of 220 g kg −1 , values that are similar to those reported by Elizalde et al 13 and Alzueta et al 15 in freeze‐dried forage samples and by Yu et al 16 in oven dried forage samples.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…In the present study, this fraction ranged from 1.5 to 7.3 g kg −1 DM, averaging 4.6 g N kg −1 DM (Table 1). When expressed as a proportion of total N, fraction A varied between 80 and 390 g kg −1 , with a mean value of 220 g kg −1 , values that are similar to those reported by Elizalde et al 13 and Alzueta et al 15 in freeze‐dried forage samples and by Yu et al 16 in oven dried forage samples.…”
Section: Resultssupporting
confidence: 85%
“…However, although total N or CP feed concentration has been successfully estimated by NIRS,10 little information describing the accuracy of NIRS prediction for CNCPS protein fractions is available 11, 12. Moreover, N fractions have been studied in silages,11 tall fescue, alfalfa and bromegrass fresh forages,13 tropical grasses,14 common vetch forage15 and alfalfa and timothy forages 16. However, as far as we know, information on N fractions of forages harvested from botanically heterogeneous permanent meadows is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…These high values correspond to the values reported for soybeans (567.0 g/kg CP) by Bertipaglia et al (2008). Alzueta et al (2001) reported a B2 fraction value of 337.0 g/ kg CP for the common vetch (Fabaceae), and Cazzato et al (2012) showed a B2 fraction value of 346.0 g/kg CP for lupines; both of these results corresponded with the results of our study. A very strong correlation (P<0.0001) was confirmed between fraction B2 and CP (r = 0.891; Fig 1) and B3 and IP (r = 0.836; Fig-2).…”
Section: Resultssupporting
confidence: 82%
“…This value is close to the fraction A value found by Cazzato et al (2012) for lupines. Alzueta et al (2001) determined that the fraction A content in legumes Vicia sativa L., vetch forage conventionally used as the animal feeds (Swain et al, 2016), ranged from 211.0 to 329.0 g/kg CP. The fraction A for our results of grain meals, rapeseed feeds, pasture forages and silages achieved mean values of 144.9, 206.8, 296.3 and 468.2 g/kg CP, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Total N and N distributed in the leaf and stem fractions are grass-specific and change in response to factors like fertilization rate and harvest date (Archibeque et al, 2001;Johnson et al, 2001), maturity at harvest (Elizalde et al, 1999;Alzueta et al, 2001), and postharvest processing (Agbossamey et al, 1998;Archibeque et al, 2002). Archibeque et al (2002) reported interactions between urea N entry rate in steers and intake of protein fractions from 3 grass hays.…”
Section: Introductionmentioning
confidence: 97%